Case Report: Neonatal onset intractable diarrhea and hypoproteinemia due to intestinal malrotation and chronic midgut volvulus - Zheng, Cuifang; Sun, Song; Gong, Ying; Miao, Shijian; Dong, Kuiran; Huang, Ying (Frontiers in Pediatrics, 2025)
Congenital diarrhea and enteropathies (CODEs) are a rare heterogeneous group of inherited disorders that typically present with severe chronic diarrhea during the first weeks of life. As a broad range of illnesses can present similarly in infants, establishing a definitive cause for CODEs is challenging. In this report, two infants were suspected to have CODE, with neonatal-onset chronic diarrhea and protein-losing enteropathy finally found to be due to intestinal malrotation and chronic midgut volvulus. Although the disease onset time was during the neonatal period, the typical findings of intestinal malrotation and volvulus were not present. Following the diagnostic approach for CODEs, both patients underwent extensive examinations without a definitive diagnosis. Intestinal malrotation was incidentally detected by an abdominal CT examination. After surgical correction of the underlying malrotation (Ladd's procedure), both infants had resolution of their diarrhea and hypoalbuminemia.